SAT0680 The development and validation of interstitial lung disease prediction models in three international mixed connective tissue disease cohorts: the norwegian mctd cohort, the hungarian mctd cohort and the mctd cohort from minnesota, us. (12th June 2018) - Reiseter, S.; Ungprasert, P.; Gunnarsson, R.; Molberg, Ø.; Lund, M.B.; Aaløkken, T.M.; Szodoray, P.; Bodolay, E.
Abstract : Background: Mixed Connective Tissue Disease (MCTD) is characterised by the presence of anti-RNP antibodies with clinical features also found in SSc, SLE and IIM. There is an ongoing debate of MCTD's position as a CTD. A substancial proportion of MCTD patients develop Interstitial Lung Disease (ILD). Objectives: This study was conducted with the aims to explore the value of MCTD diagnosis and risk assessment by developing and validating ILD prediction models. Methods: Multivariable logistic regression analyses were performed in 3 international MCTD cohorts. ILD prediction model development from clinical and laboratory parameters was performed in the Norwegian MCTD cohort (n=119). External validation of the models were performed in the Hungarian MCTD cohort (n=196) and the MCTD cohort from Minnesota, US (n=50). ILD was diagnosed by chest CT examination. Results: The cohort characteristics are presented in table 1. An ILD prediction model including Pulmonary Function Test (PFT) results (table 2) and excluding PFT results was developed. The Hosmer-Lemeshow goodness of fit test (HL test) was. 31 and. 71 and the ROC was. 83 and. 78 respectively. The ILD prediction model including DLCO <60% was validated in the Hungarian MCTD cohort and showed good calibration and discrimination (HL test=0.95 and ROC=0.82). The ILD prediction model excluding PFT results showed good calibration and discrimination in both the Hungarian MCTD cohort (HL test=0.72 and ROC=0.80) and the MCTD cohort from Minnesota (HL test=0.96 and ROC=0.67). Conclusions: The cohorts have different characteristics. Despite these differences the ILD prediction models developed in the Norwegian MCTD cohort have shown external validity when assessed in the Hungarian MCTD cohort and the MCTD cohort from Minnesota. Risk factors of ILD in MCTD patients are high levels of anti-U1 RNP antibodies, absence of arthritis and increasing age. The successive ILD prediction across different MCTD cohorts strengthens the value of MCTD diagnosis and anti-RNP antibody detection in clinical practice. Disclosure of Interest: None declared